DEVELOPMENT OF RELIABILITY, AVAILABILITY AND MAINTAINABILITY MODEL FOR RECIPROCATING COMPRESSOR IN MRCSB - Abdullah, Kamal Hanafi (IRC, 2021)
Reliability, Availability and Maintainability (RAM) analysis help in assessing and improving the performance of an equipment.